Fresno County Bar Association and American Civil Liberties Union Celebrate the Constitution at Fresno City College - Watkins, Howard::::::::: (1988)
Close-up of Berkeley Daily Gazette Headline "UC STRIKE IS ON; SIT-INS OUT OF JAIL